Acute heart failure following myocardial infarction: complement activation correlates with the severity of heart failure in patients developing cardiogenic shock. (9th February 2018) - Orrem, Hilde L.; Nilsson, Per H.; Pischke, Søren E.; Grindheim, Guro; Garred, Peter; Seljeflot, Ingebjørg; Husebye, Trygve; Aukrust, Pål; Yndestad, Arne; Andersen, Geir Ø.; Barratt‐Due, Andreas; Mollnes, Tom E.
Abstract: Aims: Heart failure (HF) is an impending complication to myocardial infarction. We hypothesized that the degree of complement activation reflects severity of HF following acute myocardial infarction. Methods and results: The LEAF trial (LEvosimendan in Acute heart Failure following myocardial infarction) evaluating 61 patients developing HF within 48 h after percutaneous coronary intervention‐treated ST‐elevation myocardial infarction herein underwent a post hoc analysis. Blood samples were drawn from inclusion to Day 5 and at 42 day follow‐up, and biomarkers were measured with enzyme immunoassays. Regional myocardial contractility was measured by echocardiography as wall motion score index (WMSI). The cardiogenic shock group ( n  = 9) was compared with the non‐shock group ( n  = 52). Controls ( n  = 44) were age‐matched and sex‐matched healthy individuals. C4bc, C3bc, C3bBbP, and sC5b‐9 were elevated in patients at inclusion compared with controls ( P  < 0.01). The shock group had higher levels compared with the non‐shock group for all activation products except C3bBbP ( P  < 0.05). At Day 42, all products were higher in the shock group ( P  < 0.05). In the shock group, sC5b‐9 correlated significantly with WMSI at baseline ( r  = 0.68; P  = 0.045) and at Day 42 ( r  = 0.84; P  = 0.036). Peak sC5b‐9 level correlated strongly with WMSI at Day 42 ( r  = 0.98; P  = 0.005). Circulating endothelial cell activation markers sICAM‐1 and sVCAM‐1 were higher in the shock group during the acute phase ( P  < 0.01), and their peak levels correlated with sC5b‐9 peak level in the whole HF population ( r  = 0.32; P  = 0.014 and r  = 0.30; P  = 0.022, respectively). Conclusions: Complement activation discriminated cardiogenic shock from non‐shock in acute ST‐elevation myocardial infarction complicated by HF and correlated with regional contractility and endothelial cell activation, suggesting a pathogenic role of complement in this condition.